2019
DOI: 10.1021/acs.jpca.9b07556
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Optimization of Mixed-Reference Spin-Flip Time-Dependent Density Functional Theory (MRSF-TDDFT) for Vertical Excitation Energies and Singlet–Triplet Energy Gaps

Abstract: The mixed-reference spin-flip (MRSF) time-dependent density functional theory (TDDFT) method eliminates the notorious spin contamination of SF-TDDFT, thus enabling identification of states of proper spin-symmetry for automatic geometry optimization and molecular dynamics simulations. Here, we analyze and optimize the MRSF-TDDFT in the calculations of the vertical excitation energies (VEEs) and the singlet−triplet (ST) gaps. The dependence of the obtained VEEs and ST gaps on the intrinsic parameters of the MRSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 71 publications
1
57
0
Order By: Relevance
“…As the current implementation of MRSF also utilizes the collinear formalism, it was shown that MRSF requires more exact exchange contribution (such as BHHLYP). 34 Therefore, all the calculations were carried out using the BH&HLYP. The effect of B3LYP on dynamics shall be also discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…As the current implementation of MRSF also utilizes the collinear formalism, it was shown that MRSF requires more exact exchange contribution (such as BHHLYP). 34 Therefore, all the calculations were carried out using the BH&HLYP. The effect of B3LYP on dynamics shall be also discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…329,330 There have been various attempts to find a more theoretically appealing solution to this conundrum by adding additional determinants to the excitation space in order to restore Ŝ2 symmetry. 27 Methods developed along these lines include a fully spin-complete version of SF-TDDFT, 329 which adds the minimal number of additional determinants needed to obtain Ŝ2 eigenstates (based on the equation-ofmotion formalism), 77 and also a "mixed-reference" spin-flip (MRSF) approach, which uses a combination of high-spin and low-spin S + 1 reference states to generate target states with spin S. [331][332][333][334][335][336] Although the MRSF-TDDFT excitation manifold is not formally spin-complete, in practice the spin contamination is very small. 331 The analytic gradient 334 and nonadiabatic derivative couplings 335 for MRSF-TDDFT have recently been formulated, facilitating nonadiabatic molecular dynamics simulations.…”
Section: Conical Intersectionsmentioning
confidence: 99%
“…12,38,39 Although some NMD simulations using SF-TDDFT have been reported using this approach, 21,39-46 a more reliable remedy is to remove the spin contamination directly. This can be done either exactly, by construction, [9][10][11][12] or else approximately, [47][48][49][50][51] but these procedures are not yet in widespread use.…”
Section: B Sf-tddftmentioning
confidence: 99%